1996
DOI: 10.1002/j.1460-2075.1996.tb00438.x
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage of sterol regulatory element binding proteins (SREBPs) by CPP32 during apoptosis.

Abstract: Cellular cholesterol homeostasis is controlled by sterol‐regulated proteolysis of membrane‐bound transcription factors called sterol‐regulatory element binding proteins (SREBPs). CPP32, a cysteine protease, was shown previously to cleave SREBP‐1 and SREBP‐2 in vitro at an aspartic acid between the basic helix‐loop‐helix leucine zipper domain and the first trans‐membrane domain, liberating a transcriptionally active fragment. Here, we show that CPP32 exists in an inactive 32 kDa form in Chinese hamster ovary (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
227
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 298 publications
(232 citation statements)
references
References 33 publications
5
227
0
Order By: Relevance
“…Moreover, we showed that apoptosis induced by MT-21 is dependent on caspase activation. Caspase-3 normally exists in the cytosolic fraction of cells as an inactive precursor, and it is activated proteolytically when cells are signaled to undergo apoptosis (Schlegel et al, 1996;Wang et al, 1996). The 32 kDa precursor form of caspase-3 is cleaved at two aspartic residues and yield an active caspase-3 consisting of two proteolytic fragments, 20 kDa and a 12 kDa (Nicholson et al, 1995;Wang et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we showed that apoptosis induced by MT-21 is dependent on caspase activation. Caspase-3 normally exists in the cytosolic fraction of cells as an inactive precursor, and it is activated proteolytically when cells are signaled to undergo apoptosis (Schlegel et al, 1996;Wang et al, 1996). The 32 kDa precursor form of caspase-3 is cleaved at two aspartic residues and yield an active caspase-3 consisting of two proteolytic fragments, 20 kDa and a 12 kDa (Nicholson et al, 1995;Wang et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The biological significance of these proteolytic cleavages and their relationship with the ensuing apoptotic morphology is often not known. Caspase-3 is responsible, either wholly or in part, for the proteolytic cleavage of a large number of substrates during apoptosis, including PARP, DNA-dependent protein kinase (DNA-PK), U1-70 kDa, heteronuclear ribonucleoproteins C1 and C2, sterol regulatory binding proteins, D4-GDP dissociation inhibitor, huntingtin, and almost certainly retinoblastoma protein (Rb) [104][105][106][107][108][109][110][111] (Table 3). A common feature of all these substrates is the presence of a DXXD motif (Table 3), similar to that originally described in PARP [68].…”
Section: Protein Substrates Cleaved By Caspases During the Execution mentioning
confidence: 99%
“…Activation of the Apaf-1/cas-9 complex appears to be a common pathway employed by diverse stimuli that induce apoptosis in mammalian cells (Li et al, 1997). Cas-3 usually exists in the cytoplasm as an inactive precursor that becomes proteolytically activated in cells undergoing apoptosis (Schlegel et al, 1996;Wang et al, 1996). Cas-3 is activated by multiple cleavages of its 32 kDa precursor form to generate the 17/11 kDa or 20/11 kDa active forms (Nicholson et al, 1995;Wang et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Cas-3 usually exists in the cytoplasm as an inactive precursor that becomes proteolytically activated in cells undergoing apoptosis (Schlegel et al, 1996;Wang et al, 1996). Cas-3 is activated by multiple cleavages of its 32 kDa precursor form to generate the 17/11 kDa or 20/11 kDa active forms (Nicholson et al, 1995;Wang et al, 1996). Other ®ndings that active cas-3 cleaves cas-3 has indicated that cas-3 can be activated through autocatalysis .…”
Section: Introductionmentioning
confidence: 99%